(untitled) (Journal of Plant Disease Sciences, 2019)
Field experiments were conducted at Rice Research Station, Moncompu, Alappuzha, Kerala for five consecutive seasons of Rabi 2012-13, Kharif, 2013, Rabi, 2013-14, Kharif, 2014 and Rabi, 2014-15 with the objective of evaluation of efficiency of newer and commercially available fungicides against sheath of blight rice. Out of seven fungicides tested, Tebuconazole (Folicur 250 EC) @ 1.5 ml/l was found most effective followed by Pencycuron (Monceren 250 SC) and Tebuconazole 50% + Trifloxystrobin 25% (Nativo 75 WG).